Design of intelligent neuro-supervised deep learning networks to analyze brain electrical activity rhythms of Parkinson’s disease model - Sana Ullah Saqib; Shih-Hau Fang; Muhammad Asif Zahoor Raja; Kottakkaran Sooppy Nisar; Muhammad Shoaib (Cognitive Neurodynamics, 2026)

Identification and functional verification of resistance genes against Lily bulb virus-1 (LbV-1) in Lilium: Insight from sRNA sequencing and transcriptomic profiling - Nisar Uddin; Xia Li; Noor Muhammad; Muhammad Shahid; Adil Hussain; Lili Zhang; Daochen Zhu (Plant Science, 2026)

Retraction notice to ‘Nano-remediation technologies for the sustainable mitigation of persistent organic pollutants’ [Environ. Res. 211 (2022) 113060] - Liu Fei; Muhammad Bilal; Sarmad Ahmad Qamar; Hafiz Muhammad Imran; Areej Riasat; Muhammad Jahangeer; Misbah Ghafoor; Nisar Ali; Hafiz M.N. Iqbal (Environmental Research, 2026)

Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Numerical study of the impact of marine independent and coupled motions on flow boiling characteristics in helical tubes - Nisar Ali; Haozhi Bian; Ruihan Jing; Muhammad Aaqib Zaidi; Qianru Liu; Zixiang Ye (Annals of Nuclear Energy, 2026)

Retraction Note: Bio-Graphene Foam: A Robust Solution for Adsorptive and Sustainable Chlorophenol Removal from Wastewater - Sidra; Muhammad Hamid khan; Wang Jin Quan; Shakeel Ahmad; Jingling Ji; Xinhua Xiao; Haseen Ullah; Arif Nawaz; Farman Ali; Nisar Ali (Water, Air, & Soil Pollution, 2026)

Retraction notice to “Environmental impacts of hazardous waste, and management strategies to reconcile circular economy and eco-sustainability” [Sci. Total Environ. 807 (2022) 150856] - Zhen Zhang; Muhammad Zeeshan Malik; Adnan Khan; Nisar Ali; Sumeet Malik; Muhammad Bilal (Science of The Total Environment, 2026)

Retraction notice to “Effective exploitation of anionic, nonionic, and nanoparticle-stabilized surfactant foams for petroleum hydrocarbon contaminated soil remediation” [Sci. Total Environ. 704 (2020) 135391] - Nisar Ali; Muhammad Bilal; Adnan Khan; Farman Ali; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Bach transcription factors: Emerging molecular regulators for oxidative stress-mediated skin responses and protection - Aneela Bashir; Mei Wang; Mengqi Liu; Jianzhou Cui; Muhammad Farrukh Nisar; Canliang Yan; Julia Li Zhong (Journal of Photochemistry and Photobiology B: Biology, 2026)

Investigation the epidemiological transition of ebola virus under contagious population with sustainable extended fractional operator - Peiluan Li; Rui Qiao; Muhammad Farman; Changjin Xu; Miaoran Yao; Kottakkaran Sooppy Nisar; Yizhen Qu (Mathematical Biosciences, 2026)

In vitro regeneration and biotechnological advances in tissue culture of Zingiber officinale Roscoe: a comprehensive review - Nisar Ahmad Zahid; Uma Rani Sinniah; Muhammad Asyraf Md Hatta; Dzarifah Zulperi; Jutta Papenbrock; Mansor Hakiman (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

The Methodological Evolution of the Water-Food-Energy Nexus Index in Agriculture: A Systematic Review - Nisar Muhammad; Rashid Farooq; Khan Zaib Jadoon; Ghufran Ahmed Pasha (Water Resources Management, 2026)
The Water-Food-Energy (WFE) nexus has become a central framework for addressing resource sustainability in agriculture, yet its operationalization increasingly relies on composite indices whose methodological foundations remain fragmented. This study presents the first systematic and critical review of the Water-Food-Energy Nexus Index (WFENI) applied in agricultural systems. Following a rigorous PRISMA-guided protocol, we analyzed 21 peer-reviewed studies to examine indicator selection, index construction, weighting schemes, and validation practices. The review reveals a clear methodological evolution from early resource-efficiency metrics toward expanded frameworks that integrate environmental, climate, and emission dimensions. While normalization approaches are largely standardized, substantial divergence exists in weighting and aggregation, marking a gradual shift from equal and expert-based weights toward data-driven and optimization-based methods. However, a critical “robustness gap” persists: the vast majority of studies lack formal sensitivity or uncertainty analysis, raising serious concerns about reliability. This review systematically maps these methodological trends and outlines a strategic agenda for future research, advocating for the institutionalization of robustness testing, dynamic modeling, and expanded system boundaries to enhance the rigor and policy relevance of agricultural sustainability assessments.

Recent Advances in p-Type Nickel Oxide (NiO) for Solar-Light-Driven Photocatalytic Degradation of Organic Pollutants - Mansoor sultan; Nisar Ali; Muhammad Naseem; Shah Ihsan; Mazharul islam; Abdul kareem; Shahbaz Khan; Bakht Muhammad Khan; Fawad khan; Farman Ali; Adnan Khan; Rayya Ahmed Al Balushi; et al. (Water, Air, & Soil Pollution, 2026)

In-silico screening of anti-cancer natural compounds targeting NF-κB as identification of potential therapeutic inhibitor - Jarin Tasnim; Md. Mehedi Hasan; Qandeel Fatima; Laiba Rashid; Sarnop Sarker; Khan Rajib Hossain; Mamoona Nisar; Md. Tamzid Hossain Molla; Muhammad Imtiaz Shafiq; Mohammad Taufiq Alam (In Silico Pharmacology, 2026)

Transforming soil health with biochar-driven slow-release fertilizers: Emphasis on biochar dual-function for acidification and alkalinization reclamation - Tawasul Ali; Pingyu Qiu; Ping Liu; Nisar Muhammad; Guangquan Chen; Tengfei Fu; Changsheng Peng (Journal of Environmental Chemical Engineering, 2026)

Physiological role of light modulation on poultry production, reproductions and welfare: a-systematic review - Yufei Huang; Nisar Ahmed Ujjan; Shahid Faraz Syed; Jameel Ahmed Buzdar; Fethi Ahmet Ozdemir; Muhammad Asif Arain (Veterinary Research Communications, 2026)

Mathematical analysis of air pollution dynamics system for emission controls and air filtration technologies with caputo derivative - Muhammad Farman; Khadija Jamil; Saba Jamil; Kottakkaran Sooppy Nisar; Aseel Smerat; Mohamed Hafez (Modeling Earth Systems and Environment, 2026)

Formulation Design of Glucuronoxylan-Based Stimuli-Responsive Microparticles for Zero-Order Drug Delivery - Saleha Babar; Fatima Akbar Sheikh; Syed Nasir Abbas Bukhari; Muhammad Tahir Haseeb; Arshad Ali; Nisar Ul Khaliq; Ranya Abdulrahman Alafar; Mohamed Abdelwahab Abdelgawad; Ameeduzzafar Zafar; Naveed Ahmad (Journal of Pharmaceutical Innovation, 2026)

Health hazards associated with radon present in soil of Nizampur, Khyber Pakhtunkhwa, Pakistan - Jehangir Ijaz; Yuping Su; Nisar Ahmad; Muhammad Bakhsh (Isotopes in Environmental and Health Studies, 2026)

Unveiling the superior adsorptive performance and stability of mushroom-derived biochar for the removal of p-aminoazobenzene from real and synthetic water samples: Insights from experiments and simulations - Afsar Khan; Tingting Liu; Chen Saisai; Zhang Qingyun; Savaş Kaya; Nisar Muhammad; Tao Zhengkai; Zhou Runjuan; Dayong Xu (Journal of Water Process Engineering, 2026)

Unveiling the charge transfer pathways in CuWO4/NiFe/SnWO4 coupled S-scheme heterojunction for photocatalytic dye degradation - Rimsha Aqeel; Tanveer Hussain Bokhari; Saqib Javaid; Amina Zafar; Muhammad Inayat Ullah; Muhammad Tariq Nadeem; Atia Khalid; Shafqat Karim; Ting Zhu; Amjad Nisar; Mashkoor Ahmad (Journal of Water Process Engineering, 2026)

Immuno-oncological Challenges and Chemoresistance in Veterinary Medicine: Probiotics as a New Strategic Tool - Muhammad Farrukh Nisar; Tingdong Yan; Yi Cai; Chunpeng Wan (Probiotics and Antimicrobial Proteins, 2026)

Multi-scale debris flow risk assessment using morphometrics in high-altitude catchments of Northern Pakistan - Yaseen Ullah; Muhammad Shafique; Nisar Ali Shah; Ghazanfar Ali Khattak; Sajid Ullah (Natural Hazards, 2026)

Enhancing mechanical and durability properties of bentonite-modified self-compacting concrete - Khawaja Adeel Tariq; Aashir Waleed; Jamil Ahmad; Fahad Ali; Naveed Ahmad; Muhammad Danish Nisar (Innovative Infrastructure Solutions, 2025)

Citri Reticulatae Pericarpium modulates gut microbiota: Impacts on human health - Yi Cai; Wanqing Ma; Yanhong Hou; Muhammad Farrukh Nisar; Yiyin Long; Baizhong Chen; Xuan Zhang; Liduan Huang; Guodong Zheng; Tingdong Yan; Chunpeng Wan (Food Research International, 2025)

Dynamics of lumpy skin disease with treatment and viral factor monitoring through fractional operator - Parvaiz Ahmad Naik; Aqeel Ahmad; Qazi Muhammad Farooq; Muhammad Farman; Abdul Ghaffar; Kottakkaran Sooppy Nisar; Aceng Sambas; Zhengxin Huang (Modeling Earth Systems and Environment, 2025)

Facile construction of chitosan-ternary metal selenide biopolymer-based composite for photocatalytic degradation of petroleum derive sunset yellow and acid black azo-dyes using response surface methodology RSM - Tariq Aziz; Muhammad Farhan; Adnan Khan; Nisar Ali; Javeed Azam; Sumeet Malik; Sarmad Ali; Nauman Ali; Hamayun Khan; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; Thuraya Al-Harthy (Environmental Science and Pollution Research, 2025)

226 Ra and 222 Rn activity concentrations and associated effective doses for different age groups in spring water of Harnai, Balochistan - Nisar Ahmad; Muhammad Bakhsh (Isotopes in Environmental and Health Studies, 2025)

Radiometric assessment of soil collected from apple orchards in Pishin, Balochistan and associated health hazards - Israr Ullah; Nisar Ahmad; Muhammad Bakhsh (Isotopes in Environmental and Health Studies, 2025)

Morphometric analysis of debris flow hazard and risk assessment in the mountain terrains of northern Pakistan using remote sensing and field data - Nisar Ali Shah; Muhammad Shafique; Lewis A. Owen; Yaseen AI-Mulla; Yaseen Ullah (Earth Science Informatics, 2025)

Dual approach artificial neural networks-fractional order operator to enhancing in vitro fertilization predictions and success measure - David Amilo; Khadijeh Sadri; Evren Hincal; Muhammad Farman; Kottakkaran Sooppy Nisar (Modeling Earth Systems and Environment, 2025)

Genetic analysis in a consanguineous MCPH family revealed a refinement of the MCPH12 locus and a founder effect of the recurrent CDK6 variant [c.589G>A, p.(Ala197Thr)] in the Pakistani population - Muzammil Ahmad Khan; Jasmin Blatterer; Markus Kuster; Lukas Kaufmann; Peter M. Kroisel; John B. Vincent; Muhammad Zubair; Muhammad Muzammal; Nisar Ahmad; Shakil Abbas; Wasim Shah; Muhammad Zeeshan Ali; et al. (Journal of Genetics, 2025)

Globally analysis of production of lactic acid by Lactobacillus plantarum AC11S: kinetics using Mittag-Leffler kernel via mathematical modeling - Muhammad Farman; Aqeel Ahmad; Muhammad Faheem; Kottakkaran Sooppy Nisar; Muhammad Saeed Akram; Hijaz Ahmad (Modeling Earth Systems and Environment, 2025)

Investigation of lassa fever with relapse and saturated incidence rate: mathematical modeling and control - Aqeel Ahmad; Usama Atta; Muhammad Farman; Kottakkaran Sooppy Nisar; Hijaz Ahmad; Evren Hincal (Modeling Earth Systems and Environment, 2025)

Geochemical and mineralogical characterization of Carboniferous-Triassic shales in Peninsular Malaysia: implications for hydrocarbon potential and depositional model - Alidu Rashid; Numair Ahmed Siddiqui; Abdul Halim Abdul Latiff; Nisar Ahmed; Maqsood Ahmad; Muhammad Jamil; Sohag Ali; Md. Mahmodul Islam (Carbonates and Evaporites, 2025)

Comprehensive assessment of radiological hazards in chromite mines at Khanozai and Muslim Bagh, Balochistan, Pakistan - Nisar Ahmad; Niamat Ullah; Muhammad Bakhsh; Hannan Younis (Isotopes in Environmental and Health Studies, 2025)

Superhydrophilic wettability porous materials from construction tooil/water separation applications - Muhammad Naseem; Mansoor Sultan; Mazhar ul Islam; Abdul Kareem; Nisar Ali; Ibrahim Khan; Shakeel Ahmad; Farooq nawaz; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Fuel, 2025)

Estimation and geographical mapping of enteric methane emission from large ruminants under different production systems in Pakistan - Nasir Ali; Muhammad Qamar Shahid; Nisar Ahmad; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2025)

Current mechanistic insights into Withaferin A: a promising potential adjuvant anticancer agent from Withania somnifera - Muhammad Farrukh Nisar; Chunpeng Wan; Dietrich Büsselberg; Daniela Calina; Javad Sharifi-Rad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Chaos and forecasting financial risk dynamics with different stochastic economic factors by using fractional operator - Muhammad Farman; Kottakkaran Sooppy Nisar; Mumtaz Ali; Hijaz Ahmad; Muhammad Farhan Tabassum; Abdul Sattar Ghaffari (Modeling Earth Systems and Environment, 2025)

Fe3O4@Au magnetic SERS nanotags-based vertical flow immunoassay for simultaneous detection of fumonisin B1, aflatoxin B1 and deoxnivalenol - Ruipeng Chen; Jianfeng Wu; Hui Wang; Muhammad Shemyal Nisar; Yongqi Li; Yuxuan Chen; Yu Mao; Xuemei Nan; Fan Zhang; Liang Yang; Xiangfang Tang; Jianwei Xie; et al. (Analytica Chimica Acta, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Naveed Ahmad; Nisar Ahmad; Muhammad Sajid; Kamran Rauf; Mudassar Iqbal; Muhammad Numan; Irfan Ullah; Amir Khan; Wahidah H. Al-Qahtani; Mostafa A. Abdel-Maksoud; Hamada AbdElgawad; Babar Iqbal; et al. (Plant Biosystems, 2025)

Reviewing the impact of seed-borne mycoflora on mycotoxin accumulation: A threat to lentil genetic resources - Sanam Asif; Momina Nisar; Shakir Ullah; Muhammad Naeem (Toxicon, 2025)

Role of Melatonin in Leaf Gas Exchange by Redox Regulation, K+ Homeostasis and Gene Expression in Canola Under Salinity Stress - Muhammad Ali; Muhammad Farooq; Adnan Noor Shah; Ghulam Hassan Abbasi; Salman Ahmad; Aasma Parveen; Birhanu Iticha; Muhammad Riaz; Muhammad Kamran; Fatima Nisar (Journal of Soil Science and Plant Nutrition, 2025)

Lyapunov global stability analysis and effects of serial killing on community disorder with generalized Mittag–Leffler kernel properties - Kottakkaran Sooppy Nisar; Aqeel Ahmad; Muhammad Farman; Evren Hincal; Rabia Sarwar (Modeling Earth Systems and Environment, 2025)

Application of fertilizers improves cadmium phytoextraction efficiency of Nasturtium officinale R.Br. grown in cadmium-contaminated water - Amjad Ali; Niaz Ali; Yansheng Gu; Nisar Ahmad; Nasar Ali; Israr Ahmad; Ajab Khan; Muhammad Anas; Hamad Ur Rehman; Asmat Ali; Muhammad Inayat Ullah khan (Environmental Monitoring and Assessment, 2025)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

Pharmacotherapeutic potential of bilobetin to combat chromium induced hepatotoxicity via regulating TLR-4, Nrf-2/Keap-1, JAK1/STAT3 and NF-κB pathway: A pharmacokinetic and molecular dynamic approach - Mahmoud El Safadi; Muhammad Faisal Hayat; Ali Akbar; Abdullah Nisar; Fuad M. Alzahrani; Khalid J. Alzahrani (Journal of Trace Elements in Medicine and Biology, 2024)

Viola stocksii: A rich source of antioxidant and anti-inflammatory flavonoid glycosides with converged therapeutic potential against SARS-CoV-2 MPro, spike trimer, and surface glycoproteins - Roshan Zamir; Shanza Munir; Humaira Yasmeen Gondal; Muhammad Nisar; Sami A. Al-Hussain; Ahmed Abbaskhan; Zain M. Cheema; Magdi E.A. Zaki; M. Iqbal Choudhary (Food Bioscience, 2024)

RETRACTED ARTICLE: Bio-Graphene Foam: A Robust Solution for Adsorptive and Sustainable Chlorophenol Removal from Wastewater - Sidra; Muhammad Hamid khan; Wang Jin Quan; Shakeel Ahmad; Jingling Ji; Xinhua Xiao; Haseen Ullah; Arif Nawaz; Farman Ali; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Anti-diabetic effects of marine natural products through redox modulation via Nrf2/HO-1 cytoprotective pathways - Muhammad Farrukh Nisar; Mingxi Li; Jialin Xu; Chunpeng Wan (Frontiers in Marine Science, 2024)
Diabetes mellitus (DM), a major global health concern, is a chronic metabolic disorder. Bioactive compounds sourced from numerous marine natural products recently have drawn attention as novel therapeutic approaches. Considering these chemicals and their role in cellular redox modulation by involving the nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway, the current study attempts to highlight their anti-diabetic effects and the molecular mechanisms involved. Reactive oxygen species (ROS)-mediated oxidative stress, inflammation, and cellular damage are linked to most human pathologies specifically DM. The Nrf2/HO-1 pathway is a key defense mechanism developed by the cells to combat ROS burst. Marine natural compounds have strong pharmacological potential in triggering cellular antioxidant defense mechanisms by declining oxidative damage and inflammation linked to DM. How marine natural products potentially alleviate DM specifically type 2 diabetes (T2D) and its related issues is especially focused on. The literature was thoroughly analyzed to open a discussion about specific marine compounds and their well-established anti-diabetic effects to elucidate possible therapeutic applications. Furthermore, opportunities and the pros and cons of using these marine bioactive compounds as complementary treatment for DM are also discussed. The diverse characteristics of marine natural products, specifically with regard to redox control, offer promising opportunities for drug discovery and therapeutic interventions in clinical trials.

Handwashing basins and healthcare associated infections: Bacterial diversity in biofilms on faucets and drains - Claire Hayward; Kirstin E. Ross; Melissa H. Brown; Muhammad Atif Nisar; Jason Hinds; Tamar Jamieson; Sophie C. Leterme; Harriet Whiley (Science of The Total Environment, 2024)

Failure mechanism of a massive fault–controlled rainfall–triggered landslide in northern Pakistan - Muhammad Tayyib Riaz; Muhammad Basharat; Khawaja Shoaib Ahmed; Yasir Sirfraz; Amir Shahzad; Nisar Ali Shah (Landslides, 2024)

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Carbon based nanocomposites, surface functionalization as a promising material for VOCs (volatile organic compounds) treatment - Farooq Nawaz; Muhammad Ali; Shakeel Ahmad; Yang Yong; Suhaib Rahman; Muhammad Naseem; Sadam Hussain; Abdul Razzaq; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Chemosphere, 2024)

Potato Chip Varietal Analysis: a Comparative Evaluation Based on Potato Cultivars - Talha Khalil; Muhammad Haroon; Sumaira Miskeen; Shehla Sammi; Muhammad Jahangir; Sara Najeeb; Kainat Nisar; Arsalan Khan; Muhammad Liaquat; Imran Khan; Jae-Won Ha (Potato Research, 2024)

Retraction Note: pH-responsive CAP-co-poly(methacrylic acid)-based hydrogel as an efficient platform for controlled gastrointestinal delivery: fabrication, characterization, in vitro and in vivo toxicity evaluation - Syed Ahmed Shah; Muhammad Sohail; Muhammad Usman Minhas; Nisar-ur-Rehman; Shahzeb Khan; Zahid Hussain; Mudassir; Arshad Mahmood; Mubeen Kousar; Asif Mahmood (Drug Delivery and Translational Research, 2024)

Tailoring structural and optical properties of Cu(II)-induced MgAl2O4 nanoparticles and their response to toxic dyes under solar illumination - Muhammad Javed; Naeem Akbar; Ayaz Arif Khan; Asad Masood; Naeem Ahmed; Muhammad Junaid Khan; Nisar Ahmed; Said Nasir Khisro; Muhammed Ali Shaikh Abdul Hameed (Environmental Science and Pollution Research, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Integrated study for assessing groundwater dynamics of the Dehdan village, Haripur Basin, Pakistan - Umair Bin Nisar; Siddique Akhtar Ehsan; Muhammad Imran Rafiq; Muhammad Rizwan Mughal (Journal of Applied Geophysics, 2024)

Designing and synthesis of perovskite nanocrystals: a promising wide-spectrum solar light–responsive photocatalyst and lead ion sensor - Nisar Ali; Shakeel Ahmad; Arif Nawaz; Manzoor Khan; Aman Ullah; Muhammad Idrees; Adnan Khan; Wilayat Khan (Environmental Science and Pollution Research, 2024)

Dietary nano-Selenium supplementation improves growth performance, nutrient digestibility and hematology in Cirrhinus mrigala fingerlings - Nisar Ahmad; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Muhammad Mahmood (Journal of Trace Elements in Medicine and Biology, 2024)

Melamine-based hyper-cross-linked resin for efficient removal of total petroleum hydrocarbons (C10–C32) from aqueous solutions - Muhammad Ilyas; Nisar Ullah; Muhammad Mansha; Mazen K. Nazal (Environmental Monitoring and Assessment, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Solar Light Assisted Metal Selenide-Chitosan Nanoparticles from Structure Tailoring to Photocatalytic Mineralization of Selected Industrial Dyes - Javeed Azam; Muhammad Farhan; Adnan Khan; Tariq Aziz; Nauman Ali; Hamayun Khan; Sumeet Malik; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Assessment of water quality using entropy-weighted quality index, statistical methods and electrical resistivity tomography, Moti village, northern Pakistan - Umair Bin Nisar; Wajeeh ur Rehman; Saher Saleem; Kashif Taufail; Faizan ur Rehman; Muhammad Farooq; Siddique Akhtar Ehsan (Journal of Contaminant Hydrology, 2024)

Local-scale integrated seismic risk assessment using satellite data and field information in Northern Pakistan - Tanveer Ahmed; Khaista Rehman; Muhammad Shafique; Nisar Ali Shah; Muhammad Waqar Azeem (Stochastic Environmental Research and Risk Assessment, 2024)

Water resource management and flood mitigation: hybrid decomposition EMD-ANN model study under climate change - Nisar Ahmad; Xu Yi; Muhammad Tayyab; Muhammad Hamza Zafar; Naureen Akhtar (Sustainable Water Resources Management, 2024)
The growing population and the rise in urbanization have made managing water a critical concern around the world in recent years. Globally, flooding is one of the most devastating natural disasters. Flood risk mitigation relies heavily on accurate and consistent streamflow forecasts. Pakistan Upper Indus Basin (UIB) is most vulnerable to flooding. Floods have become more frequent in recent decades. UIB can be divided into sub-regions due to its landscape variability, and its collective impact is most prominent in the Massam region. UIB hydrological and meteorological station observations have been used to study seasonal hydro-meteorological variations. To predict flooding, this study proposes a hybrid model combining artificial neural networks as multi-layer perceptron (MLPs) in feed-forward mode, along with empirical mode decomposition (EMD). Data collected by the surface-water hydrology project and Pakistan Meteorological Department from 1960 to 2012, 1969 to 2012, and 1972 to 2012 have been utilized from 17 locations. Statistical parameters and Nash–Sutcliffe Efficiency were measured to analyze the model’s prowess. As a result, decomposition-based models perform better than AI-based models when it comes to prediction accuracy. MLPQTP-EMD performed exceptionally better than competing AI models. The results are further validated by performing a peak value analysis during the flooding season (June–September) achieving a remarkable 91.3% score adding a 5.6% increase by EMD for input data achieving 39.3–32.3% statistical indices scores.

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Compositional shifts in rhizobacterial communities of Brassica napus under salinity stress - Muhammad Laiq; Muhammad Atif Azeem; Sara Begum; Nausheen Nazir; Zakia Ahmad; Sana Ullah; Mohammad Nisar; Abid Ullah (Applied Soil Ecology, 2024)

Insight into microplastics in the aquatic ecosystem: Properties, sources, threats and mitigation strategies - Nisar Ali; Muhammad Hamid Khan; Muhammad Ali; Sidra; Shakeel Ahmad; Adnan Khan; Ghulam Nabi; Farman Ali; Mohamed Bououdina; George Z. Kyzas (Science of The Total Environment, 2024)

Identification and validation of restricted seed color polymorphic sites in Barley (Hordeum vulgare L.) using SNPs derived CAPS markers - Murad Ali; Danish Ibrar; Zuhair Hasnain; Afroz Rais; Shahbaz Khan; Kashf Mehmood; Sami Ullah; Ali Bakhsh; Safia Gul; Muhammad Musawir Khan; Waqar Khan; Muhammad Nisar; et al. (Genetic Resources and Crop Evolution, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Therapeutic Physical Properties, Photocatalytic, and Anti-bacterial Activities of Hydrothermally Fabricated Cu-doped ZnO NPs - Muhammad Zahid Ishaque; Yasir Zaman; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Hira Zaman; Sarmad Ali; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Effect of multiwalled carbon nanotubes on compressive behavior of concrete at elevated temperature for mass concreting - Kashan Nisar; Muhammad Shahid Siddique; Muhammad Rizwan; Syed Hassan Farooq; Muhammad Usman; Asad Hanif (European Journal of Environmental and Civil Engineering, 2023)

Retention of methyl iodide on metal and TEDA impregnated activated carbon using indigenously developed setup - Talhat Yaqoob; Masroor Ahmad; Yasir Faiz; Farman Ali; Amjad Farooq; Faisal Faiz; Attaullah Shah; Muhammad Asim Irshad; Naseem Irfan; Nisar Ali; Sahid Mehmood (Environmental Research, 2023)

Future prospects of biomass waste as renewable source of energy in Pakistan: A mini review - Waqas Ahmad; Jan Nisar; Farooq Anwar; Faisal Muhammad (Bioresource Technology Reports, 2023)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

Exogenous Application of Silicon and Sulfate Improved Drought Tolerance in Sunflowers Through Modulation of Morpho-physiological and Antioxidant Defense Mechanisms - Muhammad Nisar; Muhammad Aqeel; Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Umair Rasheed; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Fahad Mohammed Alzuaibr; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2023)

Melatonin-induced development of adventitious roots, biosynthesis of secondary cell products and greener synthesis of silver nanoparticles for biological activities using Indigofera heterantha - Irfan Ullah; Muhammad Sajid; Nisar Ahmad; Naveed Ahmad; Kamran Rauf; Rabia Khalil; Babar Iqbal; Mazhar Ali; Marcelo Carvalho Minhoto Teixeira Filho; Mohammad K. Okla; Hamada AbdElgawad; Asghar Khan; et al. (South African Journal of Botany, 2023)

Synergistic effect of microwave heating and thermosonication on the physicochemical and nutritional quality of muskmelon and sugarcane juice blend - Pinky Fatima; Muhammad Nadeem; Ashiq Hussain; Tusneem Kausar; Abdul Rehman; Tahira Siddique; Khurram Kabir; Saima Noreen; Rizwan Nisar; Haya Fatima; Sameh A. Korma; Jesus Simal-Gandara (Food Chemistry, 2023)

Interaction analysis of TRIM proteins and innate immunity mediators of common carp (Cyprinus carpio L.) to evaluate its affinity for ubiquitination and innate immune response - Muhammad Aizaz; Maryum Nisar; Rehan Zafar Paracha; Shijuan Shan; Nida Fatima Ali; Iqra Arshad; Guiwen Yang (Aquaculture, 2023)

Preparation and characterization of single perovskite microplates and its sunlight assisted photodecolorization activity, validated by response surface methodology - Arif Nawaz; Irum Naz; Muhammad Atif; Adnan Khan; Nisar Ali (Chemosphere, 2023)

The composition of planktonic prokaryotic communities in a hospital building water system depends on both incoming water and flow dynamics - Muhammad Atif Nisar; Kirstin E Ross; Melissa H Brown; Richard Bentham; James Xi; Jason Hinds; Tamar Jamieson; Sophie C Leterme; Harriet Whiley (Water Research, 2023)

Water quality, governance issues, people's perception and water distribution network management through integrated techniques under changing climate - Toqeer Ahmed; Mumtaz Ahmed; Saima Naz; Umair Bin Nisar; Muhammad Zahir (Urban Climate, 2023)

Opening a new horizon in green HRM practices with big data analytics and its analogy to circular economy performance: an empirical evidence - Ka Yin Chau; Tian Huang; Massoud Moslehpour; Waqas Khan; Qasim Ali Nisar; Muhammad Haris (Environment, Development and Sustainability, 2023)

Physical properties of multifunctional TM-doped ZnO nanorods and their photocatalytic and anti-bacterial activities - Yasir Zaman; Muhammad Zahid Ishaque; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Muhammad Imran Arshad; Muhammad Sajid; Nisar Ali; Ghulam Nabi (Environmental Science and Pollution Research, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Effects of Saccharomyces cerevisiae live cells and culture on growth and productive performance in lactating Nili-Ravi buffaloes - Mohsin Ali; Saeed Ahmed; Mubashar Ali; Nisar Ahmad; Mohammad Noman Tariq; Muhammad Usman; Ahmad Azeem Sardar (Tropical Animal Health and Production, 2023)

Solar light driven degradation of textile dye contaminants for wastewater treatment – studies of novel polycationic selenide photocatalyst and process optimization by response surface methodology desirability factor - Arif Nawaz; Muhammad Atif; Adnan Khan; Mohsin Siddique; Nisar Ali; Falak Naz; Muhammad Bilal; Tak H. Kim; Malwina Momotko; Hameed Ul Haq; Grzegorz Boczkaj (Chemosphere, 2023)

Assessment of formulation variables of poor water soluble diacerein for its improved loading and anti-inflammatory activity - Maryam Shabbir; Kashif Barkat; Muhammad Umer Ashraf; Uzair Nagra; Syed Nisar Hussain Shah (Drug Delivery and Translational Research, 2023)

Architectural complexities and morphological variations of the indus fan and its elements: Understanding of the turbidite system through seismic characterization - Ehsan ul Haq; Ji Youliang; Hadayat Ullah; Khurram Shahzad; Nisar Ahmed; Saad Ahmed Mashwani; Muhammad Zaheer (Marine and Petroleum Geology, 2023)

Nutritionally rich biochemical profile in essential oil of various Mentha species and their antimicrobial activities - Hina Fazal; Muhammad Akram; Nisar Ahmad; Muhammad Qaisar; Farina Kanwal; Gohar Rehman; Irfan Ullah (Protoplasma, 2023)

A Hematological and Histopathological Study on Diphenhydramine Nasal Nano-gel and Nano-emulgel for the Management of Allergic Rhinitis in Animal Model - Hina Javed; Syed Nisar Hussain Shah; Furqan Muhammad Iqbal; Nida Javed; Benish Saeed (AAPS PharmSciTech, 2023)

Development of reusable chitosan-supported nickel sulfide microspheres for environmentally friendlier and efficient bio-sorptive decontamination of mercury toxicant - Yonghong Han; Juan Tao; Adnan Khan; Afrasiab Khan; Nisar Ali; Sumeet Malik; Chunhao Yu; Yong Yang; Teofil Jesionowski; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Cellulose/inorganic nanoparticles-based nano-biocomposite for abatement of water and wastewater pollutants - Zhen Zhang; Abdulrazaq Ibrahim Said Ahmed; Muhammad Zeeshan Malik; Nisar Ali; Adnan khan; Farman Ali; Mohamed Osman Hassan; Badr A. Mohamed; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Defective nickel zirconium oxide mesoporous bifunctional electrocatalyst for oxygen evolution reaction and overall water splitting - Maira Sadaqat; Sumaira Manzoor; Salma Aman; Laraib Nisar; Muhammad Najam-Ul-Haq; Afzal Shah; Ahmed M. Shawky; H. Elhosiny Ali; Muhammad Naeem Ashiq; T.A. Taha (Fuel, 2023)

Effect of early feeding of L-arginine and L-threonine on hatchability and post-hatch performance of broiler chicken - Fazul Nabi; Muhammad Asif Arain; Zohaib Ahmed Bhutto; Qurban Ali Shah; Nasrullah Bangulzai; Nisar Ahmed Ujjan; Sarfaraz Ali Fazlani (Tropical Animal Health and Production, 2022)

Vitamin C and fruit quality consensus in breeding elite European strawberry under multiple interactions of environment - Muhammad Nisar ALI; Sedat SERÇE (Molecular Biology Reports, 2022)

Exploration of solid waste materials for sustainable manufacturing of cementitious composites - Hamayun Khan; Anwar Baig; Mahtab Faisal; Adnan Khan; Kashif Gul; Nauman Ali; Nisar Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Genomic constitution and relationships of Ziziphus species collected from Malakand Division, Pakistan - Nisar Uddin; Noor Muhammad; Niaz Ali; Mohammad Nisar; Mengjun Liu (Physiology and Molecular Biology of Plants, 2022)

Catalytic potential of endophytes facilitates synthesis of biometallic zinc oxide nanoparticles for agricultural application - Saddam Saqib; Amna Nazeer; Muhammad Ali; Wajid Zaman; Muhammad Younas; Asim Shahzad; Sunera; Momina Nisar (BioMetals, 2022)

Robust bioinspired surfaces and their exploitation for petroleum hydrocarbon remediation - Nisar Ali; Essoh Lionnelle Gyllye; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Extracellular vesicles and exosome: insight from physiological regulatory perspectives - Muhammad Yasir Waqas; Muhammad Arshad Javid; Muhammad Mudasser Nazir; Nasir Niaz; Muhammad Farrukh Nisar; Zahid Manzoor; Sheraz Ahmed Bhatti; Sajid Hameed; Muhammad Haseeb Khaliq (Journal of Physiology and Biochemistry, 2022)

Hazardous wastes, adverse impacts, and management strategies: a way forward to environmental sustainability - Guoqing Qian; Chuansong Duanmu; Nisar Ali; Adnan Khan; Sumeet Malik; Yong Yang; Muhammad Bilal (Environment, Development and Sustainability, 2022)

Design and Optimization of Novel Taste-Masked Medicated Chocolates of Dextromethorphan with In vitro and In vivo Taste Evaluation - Rahat Fatima Naqvi; Ahmad Khan; Muhammad Farooq Umer; Obaidullah Malik; Nisar Ahmad Shahwani (Journal of Pharmaceutical Innovation, 2022)

Electrical resistivity tomography for delineating groundwater potential zones in fractured metasedimentary rocks, Lesser Himalayas, Pakistan - Muhammad Farooq; Umair Bin Nisar; Sarfraz Khan; Tarib Jalees; Muhammad Rizwan Mughal; Liaqat Ali; Toqeer Ahmed (Journal of Earth System Science, 2022)

Greening the workforce in higher educational institutions: The pursuance of environmental performance - Qazi Muhammad Ali; Qasim Ali Nisar; Rana Zain ul Abidin; Rabia Qammar; Kashif Abbass (Environmental Science and Pollution Research, 2022)

Separation and remediation of environmental pollutants using metal–organic framework-based tailored materials - Walter Dzumbira; Nisar Ali; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Synthesis and characterization of ZnO decorated reduced graphene oxide (ZnO-rGO) and evaluation of its photocatalytic activity toward photodegradation of methylene blue - Asif Nisar; Muhammad Saeed; Majid Muneer; Muhammad Usman; Iltaf Khan (Environmental Science and Pollution Research, 2022)

Facies Analysis and Sedimentary Architecture of Hybrid Event Beds in Submarine Lobes: Insights from the Crocker Fan, NW Borneo, Malaysia - Muhammad Jamil; Numair Ahmed Siddiqui; Nisar Ahmed; Muhammad Usman; Muhammad Umar; Hamad ur Rahim; Qazi Sohail Imran (Journal of Marine Science and Engineering, 2021)
Hybrid event beds represent the combined effect of multiple geological processes, which result in complex depositional geometries and distinct facies distribution in marine environments. Previous work on hybrid event beds highlights the classification, origin, and types of hybrid facies. However, in the present study, we discuss the development of hybrid event beds in submarine lobes with an emphasis on the analysis of proximal to distal, frontal to lateral relationships and evolution during lobe progradation. Detailed geological fieldwork was carried out in the classical deep-marine Late Paleogene Crocker Fan to understand the relationship between the character of hybrid bed facies and lobe architecture. The results indicate that hybrid facies of massive or structureless sandstone with mud clasts, clean to muddy sand, and chaotic muddy sand with oversized sand patch alternations (H1–H3) are well developed in proximal to medial lobes, while distal lobes mainly contain parallel to cross-laminated clean to muddy hybrid facies (H3–H5). Furthermore, lateral lobes have less vertical thickness of hybrid beds than frontal lobes. The development of hybrid beds takes place in the lower part of the thickening upward sequence of lobe progradation, while lobe retrogradation contains hybrid facies intervals in the upper part of stratigraphy. Hence, the development of hybrid beds in submarine lobe systems has a significant impact on the characterization of heterogeneities in deep-marine petroleum reservoirs at sub-seismic levels.

Pharmacological evaluation of the gabapentin salicylaldehyde derivative, gabapentsal, against tonic and phasic pain models, inflammation, and pyrexia - Nisar Ahmad; Fazal Subhan; Nazar Ul Islam; Muhammad Shahid; Naseem Ullah; Rahim Ullah; Muhammad Khurram; Muhammad Usman Amin; Shehla Akbar; Ihsan Ullah; Robert D. E. Sewell (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Traditional and cultural uses of medicinal plant species in the flora of Kuz Abakhel, for the treatment of various ailments - Noor Muhammad; Nisar Uddin; Muhammad Khalil Ullah Khan; Muhammad Umer; Niaz Ali; Shariat Ullah (Advances in Traditional Medicine, 2021)

SSR-based population structure, molecular diversity and identity cards of Ziziphus species from Pakistan and China - Nisar Uddin; Niaz Ali; Mohammad Nisar; Mengjun Liu; Zhiguo Liu; Noor Muhammad; Inayat Ur Rahman (Genetic Resources and Crop Evolution, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

Assessment of pathogenicity of Beauveria bassiana, Metarhizium anisopliae, Verticillium lecanii and Bacillus thuringiensis var. kurstaki against Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) via diet-bioassay technique under controlled conditions - Mubashar Iqbal; Muhammad Dildar Gogi; Bilal Atta; Muhammad Junaid Nisar; Muhammad Jalal Arif; Nazir Javed (International Journal of Tropical Insect Science, 2021)

Frequency analysis of annual maximum rainfall series of fifteen meteorological observatories of Sindh, Pakistan - Zamir Hussain; Imran Rafi Khan; Maryum Nisar; Uzma Nawaz; Muhammad Shafeeq ul Rehman Khan (Arabian Journal of Geosciences, 2021)

The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Screening of different legumes for the developmental preference of Callosobruchus maculatus (Bruchidae: Coleoptera) - Muhammad Shahid Nisar; Ikram Ul Haq; Hassan Ramzan; Dalal M. Aljedani; Muhammad Qasim; Waqar Islam; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Molecular epidemiology of Coxiella Brunetii in small ruminants in Punjab, Pakistan: a novel reporting analytical cross sectional study - Muhammad Zahid Iqbal; Aneela Zameer Durrani; Jawaria Ali Khan; Nisar Ahmad; Muhammad Usman; Abdul Jabbar; Amjad Khan; Saba Usman; Ahsan Anjum; Muhammad Husnain (Tropical Animal Health and Production, 2021)

Correction to: The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Treatment of Wilms’ nephroblastoma cancer cells via EGFR targeting of dactinomycin loaded DNA-nanowires - Mirza Muhammad Faran Ashraf Baig; Chengfei Zhang; Muhammad Furqan Akhtar; Ammara Saleem; Naveed Nisar (Journal of Pharmaceutical Investigation, 2021)

Photocatalytic degradation of crystal violet dye under sunlight by chitosan-encapsulated ternary metal selenide microspheres - Waqar Ahmad; Adnan Khan; Nisar Ali; Sana Khan; Salah Uddin; Sumeet Malik; Nauman Ali; Hamayun Khan; Hammad Khan; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Dihydropyrimidones: A ligands urease recognition study and mechanistic insight through in vitro and in silico approach - Farman Ali Khan; Shahbaz Shamim; Nisar Ullah; Muhammad Arif Lodhi; Khalid Mohammed Khan; Kanwal; Farman Ali; Sahib Gul Afridi; Shahnaz Perveen; Ajmal Khan (Medicinal Chemistry Research, 2021)

Assessment of Drinking Water Sources for Water Quality, Human Health Risks, and Pollution Sources: A Case Study of the District Bajaur, Pakistan - Muhammad Haya Khan; Mohammad Nafees; Nisar Muhammad; Ubaid Ullah; Rahib Hussain; Muhammad Bilal (Archives of Environmental Contamination and Toxicology, 2021)

Petrology and geochemistry of volcanic and volcanoclastic rocks from Zhob ophiolite, North-Western Pakistan - Abdul Naeem; Andrew C. Kerr; Muhammad Ishaq Kakar; Rehanul Haq Siddiqui; Muhammad Ayoub Khan; Nisar Ahmed (Arabian Journal of Geosciences, 2021)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

A Review on Traditional Uses and Pharmacological Importance of Genus Elaeagnus Species - Nausheen Nazir; Muhammad Zahoor; Mohammad Nisar (The Botanical Review, 2020)

Attraction and retention-period of different stuffs and stuffing techniques with their active food baits for the management of peach fruit fly, Bactrocera zonata (Diptera: Tephritidae) - Muhammad Junaid Nisar; Muhammad Dildar Gogi; Muhammad Jalal Arif; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2020)

HPLC-UV characterization, anticholinesterase, and free radical-scavenging activities of Rosa moschata Herrm. leaves and fruits methanolic extracts - Nausheen Nazir; Atif Ali Khan Khalil; Mohammad Nisar; Muhammad Zahoor; Sajjad Ahmad (Brazilian Journal of Botany, 2020)

Aluminium oxide nanoparticles inhibit EPS production, adhesion and biofilm formation by multidrug resistant Acinetobacter baumannii - Saima Muzammil; Mohsin Khurshid; Iqra Nawaz; Muhammad Hussnain Siddique; Muhammad Zubair; Muhammad Atif Nisar; Muhammad Imran; Sumreen Hayat (Biofouling, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Characterization of phenolic compounds in two novel lines of Pisum sativum L. along with their in vitro antioxidant potential - Nausheen Nazir; Mohammad Nisar; Sajjad Ahmad; Syed Fazal Wadood; Tour Jan; Muhammad Zahoor; Manzoor Ahmad; Abid Ullah (Environmental Science and Pollution Research, 2020)

Photocatalytic Performance of Zinc Ferrite Magnetic Nanostructures for Efficient Eriochrome Black-T Degradation from the Aqueous Environment under Unfiltered Sunlight - Ikramullah; Nisar Ali; Farman Ali; Zeshan Ali Sheikh; Muhammad Bilal; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2020)

Photocatalytic Degradation of Congo Red Dye from Aqueous Environment Using Cobalt Ferrite Nanostructures: Development, Characterization, and Photocatalytic Performance - Nisar Ali; Amir Said; Farman Ali; Fazal Raziq; Zarshad Ali; Muhammad Bilal; Laurence Reinert; Tasleem Begum; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2020)

Microzonation map of the Abbottabad basin and immediate surroundings - Sarfraz Khan; Muhammad Waseem; Muhammad Asif Khan; Zahid Hussain; Waqas Ahmed; Ahmad Hamad Khaliq; Nisar Bin Umair; Mian Luqman Hussain (Journal of Seismology, 2020)

In-vitro and in-silico anticancer potential of taxoids from Taxus wallichiana Zucc - Mughal Qayum; Muhammad Nisar; Abdur Rauf; Imran Khan; Waqar Ahmad Kaleem; Muslim Raza; Nasiara Karim; Munawar Ahmad Saleem; Saud Bawazeer; Sengul Uysal; Gokhan Zengin; Saqib Jahan; et al. (Biologia Futura, 2020)
Introduction Natural products derived from medicinal plants provide beneficial cancer chemotherapeutic drugs. Bioactive constituents from plants are explored for their anticancer properties. Methods Three known compounds (deacetylbaccatin III, tasumatrol B, and taxawallin J) were isolated from Taxus wallichiana . Compounds were screened against four cancer cell lines, such as eA498, HepG2, NCI-H226, and MDR 2780AD. Cytotoxic activity was evaluated using MTT assay against cancer cell lines. Results Tasumatrol B showed good cytotoxic activity conducted for the improvement of inhibiting potential of these compounds against the cancer drug target protein (EGFR tyrosine kinase enzyme). The docking study showed that all compounds have binding affinities and interaction profile with the receptor tyrosine kinase. Discussion The study suggests that these compounds could be used for the discovery of novel inhibitors against the target receptors for the treatment of cancer.

Antimicrobial activities of biologically synthesized metal nanoparticles: an insight into the mechanism of action - Parveen Nisar; Nasir Ali; Lubna Rahman; Muhammad Ali; Zabta Khan Shinwari (JBIC Journal of Biological Inorganic Chemistry, 2019)

Toward GIS-Based Approach for Identification of Ecological Sensitivity Areas: Multi-Criteria Evaluation Technique for Promotion of Tourism in Soon Valley, Pakistan - Muhammad Atif Butt; Khadija Nisar; Syed Amer Mahmood; Javed Sami; Jahanzeb Qureshi; Ghulam Jaffer (Journal of the Indian Society of Remote Sensing, 2019)

Cadmium induces GAPDH- and- MDH mediated delayed cell aging and dysfunction in Candida tropicalis 3Aer - Zaman Khan; Muhammad Atif Nisar; Saima Muzammil; Saima Zafar; Inga Zerr; Abdul Rehman (Environmental Monitoring and Assessment, 2019)

RETRACTED ARTICLE: pH-responsive CAP-co-poly(methacrylic acid)-based hydrogel as an efficient platform for controlled gastrointestinal delivery: fabrication, characterization, in vitro and in vivo toxicity evaluation - Syed Ahmed Shah; Muhammad Sohail; Muhammad Usman Minhas; Nisar-ur-Rehman; Shahzeb Khan; Zahid Hussain; Mudassir; Arshad Mahmood; Mubeen Kousar; Asif Mahmood (Drug Delivery and Translational Research, 2019)

Interactive Effects of Genotype and Nitrogen on the Phenology and Yield Determination of Okra [Abelmoschus esculentus (L.)] - Saba Fatima; Muhammad Sohail Khan; Muhammad Nadeem; Ilham Khan; Kashif Waseem; Muhammad Nisar; Muhammad Iqbal (International Journal of Plant Production, 2019)

Correction to: An efficient protocol for the synthesis of highly sensitive indole imines utilizing green chemistry: optimization of reaction conditions - Bushra Nisar; Syeda Laila Rubab; Abdul Rauf Raza; Sobia Tariq; Sana Jamshaid; Ayesha Sultan; Muhammad Nawaz Tahir (Molecular Diversity, 2019)

Developing nonlinear models for sediment load estimation in an irrigation canal - Fahad Ahmed; Muhammad Hassan; Hashim Nisar Hashmi (Acta Geophysica, 2018)

Experimental and numerical investigations for optimal emitter spacing in drip irrigation - Abdul Razzaq Ghumman; Muhammad Iqbal; Sajjad Ahmed; Hashim Nisar Hashmi (Irrigation and Drainage, 2018)
With the goal of determining optimal emitter spacing in drip irrigation, experiments were performed to examine the effects of emitter discharge on the wetted perimeter and spacing of emitters. Four types of soils were investigated using emitter discharge of 1.0, 2.0, 3.0 and 4.0 l h −1 . Wetting diameter was measured at six equal time intervals of water application. An equal volume of water was applied. After 1 h of supply of water, wetted soil was cut to observe the maximum wetted width and depth. Wet soil samples were taken from every patch of 10 × 10 cm to find the percentage of moisture by the gravimetric method. Empirical equations were developed for wetted depth and radius. Additional experiments with emitter discharge of 1–18 l h −1 were performed in sandy loam to obtain more data for accurate estimation of the coefficients of the empirical equations. Two computer programs based on trial and error and the generalized reduced‐gradient non‐linear‐optimized technique were used to find values of the coefficients. Root mean square error between the measured and simulated wetted radius and depth was minimized in optimization. Optimal emitter spacing for each type of soil was determined from the recorded data, which was found to be 35, 40, 40 and 45 cm in sandy loam, loam, clayey loam and clay respectively. © 2018 John Wiley & Sons, Ltd.

Pollution and energy reduction strategy in soft drink industries - Nisar Muhammad; Mohammad Nafees; Rahib Hussain; Muhammad Haya Khan; Shah Jehan; Ubaid Ullah (Environmental Science and Pollution Research, 2018)

An efficient protocol for the synthesis of highly sensitive indole imines utilizing green chemistry: optimization of reaction conditions - Bushra Nisar; Syeda Laila Rubab; Abdul Rauf Raza; Sobia Tariq; Ayesha Sultan; Muhammad Nawaz Tahir (Molecular Diversity, 2018)

Performance evaluation of 1-D numerical model HEC-RAS towards modeling sediment depositions and sediment flushing operations for the reservoirs - Habib-ur-Rehman; Muhammad Asif Chaudhry; Usman Ali Naeem; Hashim Nisar Hashmi (Environmental Monitoring and Assessment, 2018)

Prevalence of selected pharmaceuticals in surface water receiving untreated sewage in northwest Pakistan - Aisha Khan; Dilawar Farhan Shams; Waliullah Khan; Aamir Ijaz; Muhammad Qasim; Maryam Saad; Ayesha Hafeez; Shams Ali Baig; Nisar Ahmed (Environmental Monitoring and Assessment, 2018)

Formulation Development and Evaluation of Diphenhydramine Nasal Nano-Emulgel - Hina Javed; Syed Nisar Hussain Shah; Furqan Muhammad Iqbal (AAPS PharmSciTech, 2018)

DHI evaluation by combining rock physics simulation and statistical techniques for fluid identification of Cambrian-to-Cretaceous clastic reservoirs in Pakistan - Nisar Ahmed; Perveiz Khalid; Hafiz Muhammad Bilal Shafi; Patrick Connolly (Acta Geophysica, 2017)

Erratum to: An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2017)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

Respiratory syncytial virus and influenza are the key viral pathogens in children <2 years hospitalized with bronchiolitis and pneumonia in Islamabad Pakistan - Uzma Bashir; Nadia Nisar; Yasir Arshad; Muhammad Masroor Alam; Asiya Ashraf; Hajra Sadia; Birjees Mazher Kazi; Syed Sohail Zahoor Zaidi (Archives of Virology, 2017)

Investigating the nitrogen dioxide concentrations in the boundary layer by using multi-axis spectroscopic measurements and comparison with satellite observations - Muhammad Fahim Khokhar; Munazza Nisar; Asma Noreen; Waseem Razzaq Khan; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2017)

Erratum to: An application of rock physics modeling to quantify the seismic response of gas hydrate-bearing sediments in Makran accretionary prism, offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Perveiz Khalid; Liu Xue Wei; Mustansar Naeem (Geosciences Journal, 2016)

TK1656, an L-asparaginase from Thermococcus kodakarensis, a novel candidate for therapeutic applications - Shahid Mahmood Chohan; Muhammad Atif Nisar; Naeem Rashid; Ghazaleh Gharib; Qamar Bashir; Masood Ahmed Siddiqui (Biologia, 2016)

An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2016)

Synergism of polyamines and plant growth regulators enhanced morphogenesis, stevioside content, and production of commercially important natural antioxidants in Stevia rebaudiana Bert - Shahid Akbar Khalil; Nasir Kamal; Muhammad Sajid; Nisar Ahmad; Roshan Zamir; Naveed Ahmad; Shahid Ali (In Vitro Cellular & Developmental Biology - Plant, 2016)

Seismic and well log driven structural and petrophysical analysis of the Lower Goru Formation in the Lower Indus Basin, Pakistan - Muhammad Naeem; Muhammad Kamran Jafri; Sayed S. R. Moustafa; Nassir S. AL-Arifi; Shazia Asim; Farhan Khan; Nisar Ahmed (Geosciences Journal, 2016)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan - Farah Akhtar; Muhammad Tariq Javed; Aziz-ur-Rehman; Muhammad Nisar Khan; Pervez Akhtar; Sayed Misdaq Hussain; Muhammad Sohaib Aslam; Razia Kausar; Mehwish Qamar; Monica Cagiola (Tropical Animal Health and Production, 2015)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)

Geochemical assessment of metal pollution and ecotoxicology in sediment cores along Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Nisar Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2015)

Molecular insights to explore abietane diterpenes as new LOX inhibitors - Inamullah Khan; Muhammad Nisar; Armando Zarrelli; Giovanni Di Fabio; Farah Gul; Syed Naeemuddin Gilani; Muhammad Raza Shah; Amir Zada Khan; Samiullah; Hazrat Amin (Medicinal Chemistry Research, 2013)

Monitoring trace elements generated by automobiles: air pollutants with possible health impacts - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2013)

Novel quinolyl-thienyl chalcones and their 2-pyrazoline derivatives with diverse substitution pattern as antileishmanial agents against Leishmania major - Syed Umar Farooq Rizvi; Hamid Latif Siddiqui; Muhammad Nisar Ahmad; Matloob Ahmad; Mujahid Hussain Bukhari (Medicinal Chemistry Research, 2012)

Development of geomorphologic instantaneous unit hydrograph for a large watershed - Abdul Razzaq Ghumman; Muhammad Masood Ahmad; Hashim Nisar Hashmi; Mumtaz Ahmad Kamal (Environmental Monitoring and Assessment, 2012)

Characterization of tannery effluent wastewater by proton-induced X-ray emission (PIXE) analysis to investigate their role in water pollution - Lubna Shakir; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2012)

Bovine hypodermosis—a global aspect - Murtaz-ul Hassan; Muhammad Nisar Khan; Muhammad Abubakar; Hafiz Muhammad Waheed; Zafar Iqbal; Manzoor Hussain (Tropical Animal Health and Production, 2010)

Estimation of a Unique Pair of Nash Model Parameters: An Optimization Approach - Muhammad Masood Ahmad; Abdul Razzaq Ghumman; Sajjad Ahmad; Hashim Nisar Hashmi (Water Resources Management, 2010)

Efficient regeneration and antioxidant potential in regenerated tissues of Piper nigrum L. - Nisar Ahmad; Hina Fazal; Bilal Haider Abbasi; Muhammad Rashid; Tariq Mahmood; Nighat Fatima (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)